Henry James’s Portrait of the Writer as Hero - Chapman, Sara S. author. aut Link
VII, 151 p.
Keywords: One of the subjects of deepest and most enduring interest to Henry James was the creative experience of writers and critics. This study examines James's fictions about this experience, placing them within the context of James's critical work and enabling the reader to see this body of work as James himself did: as a coherent, extended portrayal of the creative experience of the writer-critic.